Stromal-Initiated Changes in the Bone Promote Metastatic Niche Development - Xianmin Luo (Cell Reports, 2016)
More than 85% of advanced breast cancer patients suffer from metastatic bone lesions, yet the mechanisms that facilitate these metastases remain poorly understood. Recent studies suggest that tumor-derived factors initiate changes within the tumor microenvironment to facilitate metastasis. However, whether stromal-initiated changes are sufficient to drive increased metastasis in the bone remains an open question. Thus, we developed a model to induce reactive senescent osteoblasts and found that they increased breast cancer colonization of the bone. Analysis of senescent osteoblasts revealed that they failed to mineralize bone matrix and increased local osteoclastogenesis, the latter process being driven by the senescence-associated secretory phenotype factor, IL-6. Neutralization of IL-6 was sufficient to limit senescence-induced osteoclastogenesis and tumor cell localization to bone, thereby reducing tumor burden. Together, these data suggest that a reactive stromal compartment can condition the niche, in the absence of tumor-derived signals, to facilitate metastatic tumor growth in the bone.